The Effect of Suspended Solids on Phytoplankton Abundance and Water Quality Dynamics in Intensive Shrimp Ponds in Kraksaan, Probolinggo, Indonesia - Chandika Lestariaji; Aang Setyawan Anjasmara; Indra Febriantoro; Hendra Poltak; Desilina Arif; Asthervina Widyastami Puspitasari; Ahmad Yani; Akbar Falah Tantri; Saidin Saidin; Fataha Ilyas Hasan (Nekton, 2026)
Intensive cultivation of whiteleg shrimp (Litopenaeus vannamei) has the potential to increase suspended solids concentrations, which can affect water quality and phytoplankton community structure. This study aims to analyze the effect of reducing Total Suspended Solids (TSS) concentrations through the application of a filtration system on phytoplankton abundance and water quality dynamics in intensive ponds. The study was conducted in intensive shrimp ponds in Kraksaan District, Probolinggo Regency, East Java, using an observational-experimental approach comparing pond conditions without filtration, mechanical filtration, and chemical filtration. The parameters observed included TSS, phytoplankton abundance, and several water quality parameters such as temperature, clarity, pH, dissolved oxygen (DO), salinity, nitrate, and orthophosphate. The results showed that mechanical filtration was able to reduce TSS most effectively with a range of 38–47 mg/L compared to chemical filtration (57–63 mg/L) and without filtration (81–91 mg/L). The decrease in TSS was followed by an increase in water clarity and DO concentration. The highest phytoplankton abundance was found in the mechanical filtration treatment (2,870–3,084 ind/L), followed by chemical filtration (2,121–2,291 ind/L), while without filtration showed the lowest abundance (1,062–1,401 ind/L). These results indicate that reducing TSS through the filtration system increases light penetration, thus supporting phytoplankton photosynthetic activity. Overall, the application of filtration systems, especially mechanical filtration, plays an important role in improving water quality and increasing phytoplankton productivity, thus potentially supporting ecosystem stability and the sustainability of intensive vannamei shrimp farming systems.